Evolution of the Chemical Composition of Primary Salts of the Verkhnekamskoe deposit - I.I. Chaikovskiy (Учёные записки Казанского университета: Серия Естественные науки)
It was established that potassium and magnesium salts of the Verkhnekamskoe deposit (Perm region, Russia) are deposited in a linear and spasmodic manner. Sylvine setting begins only when the brine is saturated enough for deposition of rocks with KCl content of 15–25 wt. %. For carnallite, this process demands MgCl2 content of 15–30 wt. %. An insoluble residue composed of a substantially clay material entered the basin both with flood waters, during the accumulation of sylvinite and carnallite strata, and in the form of two turbid water flows that caused temporary crises of salt accumulation. The removal of pelitic material from the land determined its calcareousness and metamorphization of brines, which resulted in the absence of sulfate salts. Along with the leaching of underlying sediments by the desalinated waters (bromine sorption by clay and uncompensated bromine fractionation during the formation of high-grade ores), two effects, which led to lower values of the bromine-chlorine ratio in sylvinites and carnallites, were revealed.